Perceptions of pre-service secondary science teachers on inquiry-based science education: An analysis of the demographic variables. - García-Ruiz, Cristina; Lupión-Cobos, Teresa; Blanco-López, Ángel (Bastas, 2021)
Implementing the inquiry approach in the science classroom represents a challenge for pre-service secondary science teachers due to the perceptions they build around inquiry and determine their future teaching practice. In this work, we analyse the perceptions of 46 students of the science specialities of the Master’s Degree in Secondary Education Teaching, using the design of a questionnaire adapted from the PRIMAS project. The results obtained show some initial perceptions of the participants with a very homogeneous profile for the variables analysed, finding them favourable to the inquiry as a teaching approach, although showing some concrete difficulties. We also found some statistically significant differences regarding gender and previous academic and teaching experience. However, the prior research background associated with the science and technological degrees completed by the participants seemed not to affect their perception about inquiry. We finally raise some implications of the results obtained and give some orientation that might be useful for the initial training of secondary science teachers.
Keywords: Ciencia - Estudio y enseñanza; Profesores de ciencias - Formación profesional; Investigación activa en educación; Pre-service secondary science teachers; Teachers' perceptions; Secondary education; Inquiry-based science education